2021
DOI: 10.1002/srin.202100197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure on Second Dendrite Arm Spacing and Columnar to Equiaxed Transition of 30Cr15Mo1N Ingot

Abstract: In order to clarify the effects of pressure on the second dendrite arm spacing (SDAS) and columnar to equiaxed transition (CET) of 30Cr15Mo1N ingot, changes in solidification parameters, cooling rate and columnar dendrite tip growth rate with pressure have been investigated. A formula is proposed to obtain the quantitative correlation between pressure (≤ 2 MPa) and interfacial heat transfer coefficient: hi=(28.01P2+299.28P+1129.10)t−0.24. And then, A formula is proposed to calculate SDAS with cooling rate: λ2=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…It has been reported that the secondary dendrite arm spacing in the HNSBS ingots is closely related to the cooling rate ( R ), which can be expressed as logλ2=1.3220.77logR$log \left(\lambda\right)_{2} = 1.322 - 0.77 log R$. [ 50 ] During the cooling process of molten steel, the cooling rate constantly decreased from the edge to the center of the ingot, leading an increase in λ 2 . On the other hand, it is shown that cerium addition could reduce the secondary dendrite arm spacing of the HNSBS ingots.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the secondary dendrite arm spacing in the HNSBS ingots is closely related to the cooling rate ( R ), which can be expressed as logλ2=1.3220.77logR$log \left(\lambda\right)_{2} = 1.322 - 0.77 log R$. [ 50 ] During the cooling process of molten steel, the cooling rate constantly decreased from the edge to the center of the ingot, leading an increase in λ 2 . On the other hand, it is shown that cerium addition could reduce the secondary dendrite arm spacing of the HNSBS ingots.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the nitrogen content during the solidification of 30Cr15Mo1N ingot, the cooling rate was simulated using ProCAST (ESI Group, Paris, FR) software, following the same methodology as our previous study. [8,10] The key solidification parameters and interfacial heat transfer are presented in Figure 4. However, due to the extensive nitrogen pore defects at different heights at 15 mm from the edge, it is difficult to count the SDAS.…”
Section: Nitrogen Content and Nitrogen Solubilitymentioning
confidence: 99%
“…As a result of the positive of nitrogen during the solidification of molten steel, the nitrogen content in the residual liquid phase along the interdendritic regions is considerably higher than the initial nitrogen content. [ 8,12,31 ] To calculate the nitrogen segregation in the 30Cr15Mo1N ingot, the Clyne–Kurz model is utilized. [ 32–34 ] The nitrogen content in the residual liquid phase can be determined using the following equation: [ 35 ] α=0.25λ22VD(TLTS)$$\alpha = \frac{0.25 \left(\lambda\right)_{2} ^{2} V}{D \left(\right.…”
Section: Theoretical Basis Of Bubble Nucleation and Growthmentioning
confidence: 99%
See 2 more Smart Citations